Peace Education in Early Childhood Education (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
Early childhood education in the United States focuses on educating the youngest of our citizens. Although the age range of what is considered “early childhood” for teacher certification purposes may slightly differ from state to state, it is generally understood that early childhood is birth through age eight. In practice, early childhood education tends to specifically focus onthose children younger than primary school grades. Ideas of early childhood have evolved, shifted and transformed over time. The ideas of many theorist, philosophers and educators from Plato, Rousseau and Pestalozzi to Piaget, Vygotsky and Dewey have been addressed, debated and applied to a variety of issues in early childhood.